Investigation of the dosimetric and volumetric changes using DIR method based on CT-CBCT images in nasopharynx cancer patients - Apipunyasopon, Lukkana; Weerapong, Punnapa; Buranawanichwong, Nalinpun; Kingkaew, Sakda (Journal of Thai Association of Radiation Oncology, 2020)
Backgrounds Dosimetric and volumetric variations of tumor and relevant organs in patients with nasopharyngeal carcinoma (NPC) were observed during volumetric modulated arc therapy (VMAT). A deformable image registration (DIR) algorithm can be used to track the delivered dose and to transform the delineated contour with different image modalities. Objectives The aim of this study was to assess the usability of DIR software based on computed tomography (CT) and cone-beam CT (CBCT) images as a tool for determining the volumetric changes and its dosimetric impact of tumor and organs at risk (OARs). Materials and Methods Fifteen NPC patients with a planning CT and weekly CBCT images were retrospectively studied. The DIR software, VelocityAl 4.0, was used to deform the initial plan dose and delineate contour onto the CBCT images for determining the variation. The cumulative dose and volume of PTV-high risk (PTV-HR) and OARs can be obtained from the dose volume histogram (DVH). In this study, the dice similarity coefficient (DSC) was also used to assess the volumetric changes. Results Compared with the initial plan, the doses delivered to PTV-HR were decreased while the mean doses to oral cavity and parotid glands were increased. The volumes of oral cavity and both parotid glands were decreased during the treatment course. The correlation between the DSC of both parotid glands and the treatment date was 0.743. Conclusion The DIR software based on CT-CBCT images can be used to investigate the variations of dose and volume during the treatment period for NPC patients in clinical practice.